Pengaruh Kemandirian Belajar dan Efikasi Diri Terhadap Pemahaman Akuntansi Siswa - Merdekawati, Ana; Fatmawati, Fatmawati (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The subject of accounting is one of the subjects that is considered difficult and requires student interest in learning so it is not surprising that student learning achievement is relatively low. This is because students' mastery of accounting subjects is still low. This study aims to determine the effect of learning independence and self-efficacy on the understanding of trading company accounting for students at SMA Negeri 1 Moyo Utara. This type of research is associative research with 56 respondents who were determined by the census method. Data collection techniques are questionnaires and documentation. Data collection tool uses a questionnaire. Analysis of the data used is multiple linear regression. The results showed that learning independence and self-efficacy variables had a positive and significant effect both partially and simultaneously on students 'understanding of accounting, and self-efficacy variables were the most dominant influence on students' understanding of accounting in the accounting material of trading companies. Based on the coefficient of determination, the variables of learning independence and self-efficacy contributed 82.60% to the understanding of student accounting. Based on the results of the study, it is suggested to teachers and students to be able to work together to create a quality learning process so that students can improve their understanding of the material being studied.